Diagnosis of diabetes mellitus based on 11 health risk factors using backpropagation - Arifin, Fatchul (Tanjung Malim, 2021)
Diagnosis of diabetes mellitus based on 11 health risk factors using backpropagation by Arifin, Fatchul